Structure-destabilizing mutations unleash an intrinsic perforation activity of antiapoptotic Bcl-2 in the mitochondrial membrane enabling apoptotic cell death - Ping Gao; Zhi Zhang; Rui Wang; Li Huang; Hao Wu; Zhenzhen Qiao; Xiaohui Wang; Haijing Jin; Jun Peng; Lei Liu; Quan Chen; Jialing Lin (Mitochondrial Communications, 2023)
Bcl-2 and Bax share a similar structural fold in solution, yet function oppositely in the mitochondrial outer membrane (MOM) during apoptosis. The proapoptotic Bax forms pores in the MOM to trigger cell death, whereas Bcl-2 inhibits the Bax pore formation to prevent cell death. Intriguingly both proteins can switch to a similar conformation after activation by BH3-only proteins, with multiple regions embedded in the MOM. Here we tested a hypothesis that destabilization of the Bcl-2 structure might convert Bcl-2 to a Bax-like perforator. We discovered that mutations of glutamate 152 which eliminate hydrogen bonds in the protein core and thereby reduce the Bcl-2 structural stability. These Bcl-2 mutants induced apoptosis by releasing cytochrome c from the mitochondria in the cells that lack Bax and Bak, the other proapoptotic perforator. Using liposomal membranes made with typical mitochondrial lipids and reconstituted with purified proteins we revealed this perforation activity was intrinsic to Bcl-2 and could be unleashed by a BH3-only protein, similar to the perforation activity of Bax. Our study thus demonstrated a structural conversion of antiapoptotic Bcl-2 to a proapoptotic perforator through a simple molecular manipulation or interaction that is worthy to explore further for eradicating cancer cells that are resistant to a current Bcl-2-targeting drug.